COMPOSITION AND SEASONAL FLUCTUATIONS OF ENTOMOFAUNA FROM A HILL STREAM OF PAMBA RIVER IN THE WESTERN GHATS - THOMAS, RUBY; THOMAS, K. RAJU (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
The present investigation was conducted to determine the composition of insect community from a hill stream of holy river Pamba, in the Western Ghats. Collection of both aquatic and riparian insects from the respective stream stretch was carried out during the period of January –December 2019, based on their nature and habit. A total of 25 species of insects belonging to six orders, 14 families and 20 genera were reported from the hill stream in the Western Ghats. The healthy stream supported a rich insect community, which showed population fluctuation on a seasonal basis. Substrate stability, stream drainage basin, physico-chemical parameters and the surrounding vegetation determined the composition and diversity of stream associated insects in the respected area.